Imigracja w Szwajcarii po 1945 roku – ewolucja postaw społeczeństwa i federalna polityka integracji - Pogorzelska-Kliks, Agata (Studia Europaea Gnesnensia, 2015)
The article discusses immigration in Switzerland after 1945: its dynamics and the policy of the federal government towards immigration and immigrants. An important issue addressed in the paper are relations between Helvetian Federation and European Union, especially with respect to bilateral agreements concerning free movement of people. The second part of the article is devoted to social attitudes towards immigration as well as the increasingly radical views of the right-wing groups, especially Swiss People’s Party (SVP, in French – Democratic Union of the Centre – UDC) on immigration, which is most vividly manifested in public initiatives submitted to popular vote. An analysis of the results of votes demonstrates that the attitudes of the Swiss public towards immigration are not uniform. Initiatives aimed at expelling immigrants from Switzerland are rejected, but so are proposals of laws which make obtaining Swiss citizenship easier. Furthermore, the author discusses the Federation’s immigrant integration policies, in which emphasis is put on integration on the job market or social integration, while completely ignoring political integration (granting civil rights). The final issue addressed in this paper is the analysis of a watershed in the history of immigration in Switzerland, namely the public vote of February 9th, 2014 “Against Mass Immigration” and its consequences. This has been discussed based on source texts (text of the public initiative and commentaries of politicians, sociologists and journalists).